'ANGER SWEETER THAN DRIPPING HONEY': VIOLENCE AS A PROBLEM IN THE ILIAD. (27th November 2015) - Thalmann, William G.
Abstract : Remarkably in a poem so concerned with warfare, there are prominent moments in the Iliad when it seems possible that the Trojan War can be settled and peace restored: for example, Agamemnon's three proposals that the Akhaians abandon the war and go home (Books 2, 9, and 14), the truce and single combat in Book 3, and the proposal in the Trojan assembly of Book 7 that Helen be returned to Menelaos. These episodes form a pattern of resistance, or potential counter-narrative, to what would otherwise seem a relentless progression to Troy's destruction. For the most part, therefore, they occur relatively early in the poem, when the course of events seems less determined than it does later. But twice in the late books, a character says something that, if pursued, might have led to peace. These later moments are striking because they occur even after the death of Patroklos, when alternatives to war and destruction appear to have been stripped away, and because they arise when Akhilleus has recognized something essential about human vulnerability. In both cases, the possibility of peace glimmers only faintly and then fades. But that it is raised at all so late in the narrative exemplifies how the Iliad makes a problem of violence while depicting it.